Kondisi Motivasi Belajar Mahasiswa Geografi FMIPA UNM - Suprapta Suprapta (Seminar Nasional LP2M UNM, 2017)
This article aim is expouse motivation condition of learning 0f geography student fakulty of matematic and natural science, Makassar State University on 4 and 6 semester 2017 shool years. The prominent phusing of learning motivation study beginning from staf statement that enthusiasm student to learning in several courses is low. What the his low motivation are intrinsic or extrinsic motivations, will be studied in this article. Key words: condition, motivation